2006
DOI: 10.1128/jvi.80.6.3030-3041.2006
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus Engrafted with Human Immunodeficiency Virus Type 1 (HIV-1)-Specific Epitopes: Replication, Neutralization, and Survey of HIV-1-Positive Plasma

Abstract: To date, only a small number of anti-human immunodeficiency virus type 1 (HIV-1) monoclonal antibodies (MAbs) with relatively broad neutralizing activity have been isolated from infected individuals. Adequate techniques for defining how frequently antibodies of these specificities arise in HIV-infected people have been lacking, although it is generally assumed that such antibodies are rare. In order to create an epitope-specific neutralization assay, we introduced well-characterized HIV-1 epitopes into the het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 64 publications
(82 reference statements)
7
60
1
Order By: Relevance
“…5 and 8B). Yuste et al screened 92 HIV-positive plasma samples from 47 different patients in neutralizing 4E10 epitopeengrafted SIV and found that only 4 samples possessed anti-4E10 epitope activity (73). This study highlights the fact that the 4E10 epitope is poorly immunogenic in natural infections.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 8B). Yuste et al screened 92 HIV-positive plasma samples from 47 different patients in neutralizing 4E10 epitopeengrafted SIV and found that only 4 samples possessed anti-4E10 epitope activity (73). This study highlights the fact that the 4E10 epitope is poorly immunogenic in natural infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we along with others have demonstrated that HIV-2 Env could be used as a scaffold to present HIV-1 MPER and CD4i epitopes in the context of a functional glycoprotein and that such viruses could serve as sensitive and specific probes for HIV-1-elicited epitope-specific NAbs (18,19,34,61,102 In the present study, we focused on HIV-1 V3, which continues to attract substantial attention as a target of NAbs (2,54,72,74,76,99,107). Mamounas and colleagues first demonstrated that a chimeric virus containing an HIV-2 backbone and an HIV-1 MN V3 loop was capable of infecting human T cells and showed susceptibility to HIV-1 V3-specific antiserum (64).…”
Section: Discussionmentioning
confidence: 99%
“…Although SIV is an excellent model of HIV-1, homology of the env gene between SIV and HIV-1 is low (Yuste et al, 2006), and consequently reciprocal neutralizing antibodies do not show cross-reactivity (Javaherian et al, 1992). Thus, an important limitation of the SIV/macaque model is that the protective effects of neutralizing antibodies against HIV-1 cannot be examined.…”
Section: Introductionmentioning
confidence: 99%